The Requirements for Suppliers in The Standard IATF 16949:2016 – A List of New Records and Their Impact on The Automotive Industry - Karol DĄBROWSKI; Katarzyna SKRZYPEK; Sławomir KŁOS (Communications of International Proceedings, 2021)
The automotive industry bases its functioning on the implementation of the assumptions set out in a specially developed standard. Since October 2017, automotive companies are obliged to comply with the IATF 16949:2016 standard, which replaced the previously used ISO/TS 16949 standard. The article presents list of new records and their impact on the automotive industry.
Keywords: automotive industry; IATF 16949:2016; ISO/TS 16949; standard